(untitled) (Research, Society and Development, 2022)
We present an inventory of polypore fungi (Basidiomycota; Hymenochaetales and Polyporales) with the aim of knowing the diversity of an area of 8 km2 of Brazilian Amazon rainforest, in the surroundings of HPP Sílvio Braga, in the west of Pará, where 91 species were collected (545 specimens), with 16 of these new records for the state of Pará, and 1 for America. These numbers tend to increase, given the projected occurrence of 118 species for the area. 87 species were considered occasional or rare, with only four considered frequent and none abundant. The richness observed in the study area was similar to other conservation units in the Amazon, for example, Caxiuanã National Forest (74 species). This observation, added to the potential increase in the number of species, the number of species with low representativeness (relative frequency) and the number of new records for the state, demonstrate the need to expand studies on polypore fungi in the region to learn about their biodiversity and the need for conservation of that area.